2006
DOI: 10.1159/000098327
|View full text |Cite
|
Sign up to set email alerts
|

Mild Mechanical Traumas Are Possible Risk Factors for Cervical Artery Dissection

Abstract: Background and Purpose: Cervical artery dissection (CAD) is a common cause of ischemic stroke in younger aged subjects. Retrospective studies suggest cervical manipulative therapy (CMT) and preceding infections as extrinsic risk factors for CAD. In a case-control study, we assessed a questionnaire with 7 mild mechanical traumas as potential trigger factors for CAD, including CMT and recent infections. Patients and Methods: Forty-seven consecutive patients with CAD were compared with 47 consecutive patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 42 publications
7
79
0
2
Order By: Relevance
“…This finding has also been supported in more recent reviews by Dittrich et al 79 and Thomas et al 43 In contrast, Metso et al 17 …”
Section: History Of Hypertension and Risk Factors For Cardiovascular supporting
confidence: 60%
See 1 more Smart Citation
“…This finding has also been supported in more recent reviews by Dittrich et al 79 and Thomas et al 43 In contrast, Metso et al 17 …”
Section: History Of Hypertension and Risk Factors For Cardiovascular supporting
confidence: 60%
“…79 A case study by Gilberti et al 64 reported the onset of an ICAD following "head-banging" at a rock concert, reinforcing the need to establish the mode of onset of the patient's current complaint as part of the clinical history. However, these authors did not provide any information as to whether there was a pre-existing vascular pathology or risk factors that may have contributed to the development of the ICAD.…”
Section: Onset Of Pain Related To Sudden Cervical Spine Movementmentioning
confidence: 99%
“…Most current hypotheses for sICAD acknowledge the probability of some underlying predisposing factor combined with an initiating event that is most likely a trivial trauma of some degree (Dittrich et al, 2007;Haneline and Lewkovich, 2005). Previously, however, the association of an initiating trivial trauma has been based on phenomenological information such as association of the onset of symptoms with regular events including sporting activities, sneezing, dental treatment and reversing a car (Kumar et al, 1998;Schievink, 2001;Siwiec and Solomon, 2007;Taylor and Kerry, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous dissection was defined as occurring spontaneously, after physical exertion, or a so-called minor trauma. 6 Patients with previous sCAD were not included.…”
Section: Strokementioning
confidence: 99%